2018
DOI: 10.1002/jcb.26669
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐193b‐3p regulates matrix metalloproteinase 19 expression in interleukin‐1β‐induced human chondrocytes

Abstract: Micro(mi)RNAs are small, non-coding RNA molecules known to play a significant role in osteoarthritis (OA) initiation and development, and similar to matrix metalloproteinases (MMPs), they participate in cartilage degeneration and cleave multiple extracellular matrices. The aim of this study was to determine whether the expression of MMP-19 in interleukin (IL)-1β-induced human chondrocytes is directly regulated by miR-193b-3p. Expression levels of miR-193b-3p and MMP-19 in normal and osteoarthritis (OA) human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Cartilage destruction begins when chondrocytes are stimulated by proinflammatory cytokines such as IL-1β, IL-6, IL-8, and TNF-alpha 36 , and anti-inflammatory therapies have been considered as innovative osteoarthritis approaches 27 , 37 . miR-193b-3p was shown to inhibit MMP-19 and iNOS expression in IL-1β-induced human chondrocytes by direct targeting MMP-19 38 . In this study, we found that miR-193b-3p was down-regulated in time (6 h, 12 h, 24 h)- and dose (0, 1, 5, and 10 ng/mL)-dependent manners in chondrocytes stimulated with IL-1β.…”
Section: Discussionmentioning
confidence: 97%
“…Cartilage destruction begins when chondrocytes are stimulated by proinflammatory cytokines such as IL-1β, IL-6, IL-8, and TNF-alpha 36 , and anti-inflammatory therapies have been considered as innovative osteoarthritis approaches 27 , 37 . miR-193b-3p was shown to inhibit MMP-19 and iNOS expression in IL-1β-induced human chondrocytes by direct targeting MMP-19 38 . In this study, we found that miR-193b-3p was down-regulated in time (6 h, 12 h, 24 h)- and dose (0, 1, 5, and 10 ng/mL)-dependent manners in chondrocytes stimulated with IL-1β.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to MMP-19, miR-193b-3p inhibits iNOS in human chondrocytes. miR-193b-3p promotes chondrogenic differentiation of hMSCs but is reduced in OA and in IL-1β-treated chondrocytes (53,54). Increasing miR-193b-3p expression may inhibit degradation of ECM components and moderate inflammation through regulation of iNOS (54).…”
Section: Mirs Involved In Cartilage-protective Mechanismsmentioning
confidence: 99%
“…Ramp3 is a receptor activitymodifying protein that is highly expressed during joint in ammation [83]. Cyp1b1 (a member of the cytochrome P450 enzyme family), Pcsk1n (an inhibitor of prohormone convertase 1), Dlx3 (a family member of homeobox proteins), Nkd2 (a regulator of in ammatory response), Mmp19 (a subtype of matrix metalloproteinases), Htra4 (a subtype of serine proteases), Aplnr (a G protein-coupled receptor of apelin), Tubb2b (a beta isoform of tubulin), Arg1 (a cytosolic manganese-dependent enzyme) and Clic5 (a chloride intracellular channel protein) are reported to be highly expressed under osteoarthritic condition [84][85][86][87][88][89][90][91][92][93]. Thus, these results suggest that DAE play a potential role in preventing articular cartilage degeneration and in ammation by inhibiting multiple genes involved in the pathophysiology of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%